Metagenomic analysis of the nasopharyngeal microbiomes and resistomes in asthma, COVID-19 infected, and healthy individuals - Wicaksono, Wisnu Adi; Thorsen, Jonathan; Stokholm, Jakob; Berg, Gabriele (Frontiers in Microbiology, 2026)
IntroductionThe nasopharyngeal microbiome presents an important environmental human interface and a window in the fight against chronic diseases like asthma, respiratory infections, and antimicrobial resistance. To identify the microbial structure and function, we designed a pilot study with individuals with asthma, COVID-19 infection, and healthy controls.MethodsWe compare the microbial and resistome profiles of healthy individuals, patients with asthma, and patients with PCR-confirmed COVID-19 using shotgun metagenome sequencing. Additionally, metagenome-assembled genomes were generated to assess the virulence potential of the bacteria identified in the nasopharynx.ResultsWe found different patterns in microbial diversity, richness, and structure between individuals with asthma and those who are healthy, but not for those with COVID-19. Our results revealed unexpected insights into the quite diverse nasopharynx resistome encompassing 23 distinct drug classes, mainly based on antibiotic efflux (63.9%) and antibiotic inactivation (24.6%), regardless of the disease state. The majority of the antimicrobial resistance genes (ARGs) confer resistance to multidrug (45%), followed by those genes that confer resistance to aminoglycosides, tetracyclines, polymyxin, beta-lactam, and macrolide-lincosamide-streptogramin. A high proportion of ARGs was associated with various Pseudomonas species, which was confirmed by analysing metagenome-assembled genomes. Pseudomonas brenneri exhibited the highest number of ARGs and virulence factors, indicating notable pathogenic potential.ConclusionThe study reveals distinct bacterial community compositions in healthy individuals and individuals with asthma. Pseudomonadales, particularly Pseudomonas species, contribute to the nasopharyngeal resistome. No association was found between nasopharyngeal resistome profiles and asthma development. Future research may explore airway microbial functions’ influence on asthma development.